Perancangan Ulang Progressive Cavity Pump dalam Upaya Peningkatan Laju Alir Sumur DA-01 pada Lapangan DLA - Dewi Latifatul Aini; Muhammad Taufiq Fathaddin; Hari Karyadi Oetomo (Jurnal Migasian, 2022)
The DLA field is an oil field located in Central Java. In the DLA field there are 35 producing wells. The wells in the DLA field use several types of artificial lift, namely sucker rod pump, electric submersible pump, hydraulic pumping unit and progressive cavity pump. Well DA-01 is one of three wells that use PCP (Progressive Cavity Pump). The pump uses the Moyno 40-N-095 pump type. The DA-01 well has a depth of 725 meters. The well is perforated at intervals of 720 meters to 725 meters. The well is equipped with a 7-inch diameter casing, and 2.875-inch tubing. The decline in the production rate occurred in the DA-01 well along with the production time from the well. So that the well was redesigned the installed Progressive Cavity Pump to increase its production rate. At this time the actual production rate at well DA-01 is 41.38 bfpd. Meanwhile, the optimum production rate is 234.41 bfpd. The purpose of this study was to analyze PCP in order to increase the production rate. This shows that PCP redesign is still needed to achieve the target. Before doing the redesign, the formation productivity value is needed to show whether the well is still feasible to produce or not. The redesign was carried out by analyzing the pump setting depth, submergen, pump intake pressure, total dynamic head, horse power, revolutions per minute, torque value and the type of drive head used. After the analysis is done, it takes 11 HP, with a rotation speed of 305 RPM with the drive head type R&M AA4 to achieve the optimum production rate.